Arquitetura subjacente à via férrea: relações de lugar e poder no espaço urbano de Santa Maria/RS - final do século XIX e início do XX - Blois Filho, Hugo Gomes (2018)
This work entitled Architecture underlying the railroad: place and power relations in the urban space of Santa Maria/RS – end of the XIX’s and the start of XX’s century, was aimed to analyze the power relations that interacted/interfered in the constitution of the railroad space in the city of Santa Maria/RS, whose occupation took place at the end of the 19th century. For that, the analysis proceeds from the localization phenomenon with the arrival of the railroad and consequent characterization of three places: Rio Branco Avenue – main axis connection from the urban center to the Railway Station; the “Vila Operária Belga” – a housing nucleus designed to house the administrative workers of the railroad and, finally, the “Itararé” neighborhood where were installed the workers responsible for maintaining the railroad, called "tucos" . The studies and analysis are based on authors such as Michel Foucault and Pierre Bourdieu and on the understanding of the relations of symbolic power that are established between different social groups. The analysis is structured in reference to the existing iconography, capable of revealing the architecture produced in the period, as well as its relations with the urban form. It is concluded that the architectural production, produced by the railroad workers group and the urban elite of Santa Maria, is underlying through the building elements related to the railroad deployment. Its underlying reveals us that the railroad was the pioneer, not just on Santa Maria economic development, but it also resulted in the consolidation of a differentiated architecture on its symbolic assumption.